Stretching and immobilizing a single DNA molecule on a glass surface using pressure flow in a microchannel for super-resolution imaging - Naoki Azuma; Ryotaro Suzuki; Kenji Fukuzawa; Shintaro Itoh; Hedong Zhang (AIP Advances)
Single-DNA analysis combines fluorescence microscopy with a method of stretching a single DNA molecule from its random coil shape to a linear shape. Although super-resolution imaging methods can be used for analyzing the DNA with a higher lateral resolution, these methods require several seconds to minutes to obtain a super-resolution image of the entire DNA molecule. Therefore, immobilizing the stretched DNA molecules on the substrate surface is essential for preventing the decrease in the lateral resolution caused by thermal fluctuations of the molecule. Previous studies utilized a method to use super-resolution imaging methods, in which a DNA molecule can be stretched by the surface tension of the air–liquid interface and immobilized on a glass surface treated with a silane coupling agent. However, achieving control over the stretch ratio of the DNA molecule poses challenges because of the difficulty in accurately adjusting the surface tension. In this study, we used the combination of stretching DNA molecules using pressure flow in a microchannel and immobilizing them on a glass surface treated with a silane coupling agent. Our results indicated that this method enabled the control of the stretch ratio of the molecule by adjusting the flow velocity and the super-resolution imaging while reducing thermal fluctuation by immobilizing the molecule on the surface. Combining the method with the super-resolution imaging method enables the analysis of single DNA molecules with higher accuracy.